YOGA SASTRA - Nyoman Prastika (Pascasarjana Universitas Hindu Indonesia, 2017)
This research has been designed on the phenomenology perspective, understanding the nomena behind the phenomenon of mystic praxes by the balian usada in Bali. The starting point of this study are the facts that the yoga and the usada texts contained in the lontar are ‘not yet’ fully transformed to the ‘heirs’. This causes the texts to become increasingly marginalized in the sense that they are no longer meaningful to the present generations. The results of this study show, firstly, theoretically the mystical praxes of the balian usada are actually based on the teachings of yoga as taught by Rsi Patanjali. However in practice, there has been adaptation to the pattern of tantric yoga whose elements are yantra, mudra, mantra, kuthamantra, and pranava. Secondly, the bijaksara formulations practiced by the balian usada turned out to be varied into several versions. Thirdly, the study also found the local genius of the balian usada in Bali has a strong bargaining position in interacting withthe influences coming from outside of themselves.